An Overview of Univeristy Students' Behavior in Using Tiktok On Their Daily Life - Syam, Ferawaty; Meldawati, Sri Fatta (Palakka : Media and Islamic Communication, 2022)
The main objective of this research is to explore the students' behavior in using TikTok on their daily life. This research employed descriptive survey with quantitative approach, the data were gained through online questionnaire which distributed to 26 students randomly. The data were analyzed using SPSS descriptive statistic to report the result of the survey. Based on the findings, it is reported that (1) the students is enjoying using TikTok, (2) most of the students at least using or opening the TikTok once a day (3) Entertainment video content become the most favorite content watched by the students,(4) the purpose for using TikTok is to entertain themselves, (5) there are no direct effect of using TikTok for their communication skill.